2020
DOI: 10.1002/oby.22743
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Three‐Dimensional Photonic Scan‐Derived Equations Improve Body Surface Area Prediction in Diverse Populations

Abstract: Objective Equations for predicting body surface area (BSA) produce flawed estimates, especially for individuals with obesity. This study aimed to compare BSA measured by a three‐dimensional photonic scanner (3DPS) with BSA predicted by six commonly cited prediction equations and to develop new prediction equations if warranted. Methods The 3DPS was validated against manual measurements by breadth caliper for body thicknesses measured at three anatomical sites on a mannequin. BSA was derived from 3DPS whole‐bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…When covariates were missing, these were estimated using our derived equations, as done by Williams and Leggett [ 19 ]; primary covariates, such as anthropometric variables, were derived only for the verification dataset, while secondary covariates, such as cardiac output or adipose tissue weight, were also derived for the development dataset. The body surface area (BSA) was calculated according to the Ashby–Thompson equation (not using the mostly commonly used DuBois and DuBois equation) because it was developed using a new technology (three-dimensional photonic scanner), a richer dataset (268 vs. 9 individuals) and wider BMI range (17.8–77.8 vs. 15.3–41.5 kg/m 2 ), and the authors found it improved the BSA prediction in individuals with a BMI ≥ 40 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…When covariates were missing, these were estimated using our derived equations, as done by Williams and Leggett [ 19 ]; primary covariates, such as anthropometric variables, were derived only for the verification dataset, while secondary covariates, such as cardiac output or adipose tissue weight, were also derived for the development dataset. The body surface area (BSA) was calculated according to the Ashby–Thompson equation (not using the mostly commonly used DuBois and DuBois equation) because it was developed using a new technology (three-dimensional photonic scanner), a richer dataset (268 vs. 9 individuals) and wider BMI range (17.8–77.8 vs. 15.3–41.5 kg/m 2 ), and the authors found it improved the BSA prediction in individuals with a BMI ≥ 40 [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is worth nothing that, as far as the authors are aware, no BSA prediction equation currently exists which accounts for BrSA in women. For example, equations to better estimate BSA in specific populations, including women, have been recently published (Ashby‐Thompson et al., 2020 ), and they (somewhat) overcome previous limitations with, for example, Du Bois and Du Bois equations, particularly in larger individuals. Yet, these corrected equations still do not account for variation in BrSA in women.…”
Section: Discussionmentioning
confidence: 99%
“…Body surface area (BSA) is a measure of the total surface area of the human body. Given the substantial variability in body size across individuals, BSA has emerged as a standardization tool for various clinical assessments of biological function [30]. BSA is particularly useful in children and adolescents because it gives a more accurate assessment of morphological changes during growth.…”
Section: Body Surface Areamentioning
confidence: 99%